Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile - Ferrari, Rafael R. (Zootaxa, 2017)
A taxonomic revision of Colletes Latreille species with known geographic distribution in Chile is presented. In addition to the traditional morphological approach to taxonomy, DNA barcoding was employed to facilitate sexual association and cryptic species recognition. I provide diagnoses, synonymies, geographic and floral records, and a fully-illustrated key for 31 recognized species, 23 of them previously described: C. alocochila Moure, C. atacamensis Janvier, C. atripes Smith, C. bicolor Smith, C. chusmiza Rojas & Toro, C. cognatus Spinola, C. cyanescens (Haliday), C. cyaniventris Spinola n. stat., C. flaminii Moure, C. fulvipes Spinola, C. gilvus Vachal, C. guanta Rojas & Toro, C. longiceps Friese, C. lucens Vachal, C. mastochila Moure, C. murinus Friese, C. musculus Friese, C. nigritulus Friese, C. patagonicus Schrottky, C. quelu Rojas & Toro, C. rutilans Vachal, C. sulcatus Vachal, and C. vicugnensis Rojas & Toro. In addition, eight new species are described: C. arthuri n. sp., C. coquimbensis n. sp., C. flavipilosus n. sp., C. kuhlmanni n. sp., C. nigropilosus n. sp., C. simulatus n. sp., C. toroi n. sp., and C. ventricarinatus n. sp. Lectotypes for the following species are designated: Andrena cyanescens, Colletes bicolor, C. campoi Herbst, C. chubutensis Cockerell, C. gilvus, C. lucens, C. patagonicus, C. rufosignatus Cockerell, and C. viridans Vachal. Colletes seminitidus Spinola and C. viridans are both proposed as junior synonyms of C. cyanescens, and C. araucariae Friese is considered a junior synonym of C. sulcatus. Colletes cyaniventris n. stat. is resurrected from synonymy.